Pollen morphology of eight species of stemodia (plantaginaceae) from South America - Sosa, María de las Mercedes (2011)
Fil: Sosa, María de las Mercedes. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.